Self-esteem modulates the similarity of the representation of the self in the brains of others - Moriah S. Stendel; Taylor D. Guthrie; Victoria Guazzelli Williamson; Robert S. Chavez (Communications Psychology)
Abstract Social neuroscientists have made marked progress in understanding the underlying neural mechanisms that contribute to self-esteem. However, these neural mechanisms have not been examined within the rich social contexts that theories in social psychology emphasize. Previous research has demonstrated that neural representations of the self are reflected in the brains of peers in a phenomenon called the ‘self-recapitulation effect’, but it remains unclear how these processes are influenced by self-esteem. In the current study, we used functional magnetic resonance imaging in a round-robin design within 19 independent groups of participants (total N = 107) to test how self-esteem modulates the representation of self-other similarity in multivariate brain response patterns during interpersonal perception. Our results replicate the self-recapitulation effect in a sample almost ten times the size of the original study and show that these effects are found within distributed brain systems underlying self-representation and social cognition. Furthermore, we extend these findings to demonstrate that individual differences in self-esteem modulate these responses within the medial prefrontal cortex, a region implicated in evaluative self-referential processing. These findings inform theoretical models of self-esteem in social psychology and suggest that greater self-esteem is associated with psychologically distanced self-evaluations from peer-evaluations in interpersonal appraisals.